Strategy Analysis for Reducing Stunting in Acceleration of Achievement of Sustainable Development Goals Case Study in Jember District, East Java - Maya Puspitasari, Febriana; Viphindrartin, Sebastiana; Zainuri, Zainuri (Inovbook Publications, 2024)
This study examines the strategy for reducing stunting in accelerating the achievement of sustainable development goals. The main objective is to analyze the strategy for reducing stunting in order to accelerate the achievement of sustainable development goals. The method used is a case study with a qualitative approach. Data were obtained from informants in the Discussion Group Forum, and interviews with the help of questionnaires, which were processed using SWOT analysis. SWOT analysis is a strategic planning method used to evaluate the strengths, weaknesses, opportunities and threats that occur in a project. The 2020-2024 National Medium-Term Development Plan targets stunting to reach 14% by the end of 2024, while the prevalence of stunting in Jember Regency at the end of 2023 was 29.7%. So it requires the right strategy to achieve the target. In the Discussion Group Forum held on May 28, 2024 at the Wahya Wibawagraha Pendopo, Jember Regency, various views from experts were put forward which were discussed and agreed upon in an integrity pact as a form of commitment to its implementation starting on June 1, 2024. And from in-depth interviews, information was obtained from experts, policy makers and actors who had been involved in reducing stunting in Jember Regency. This study found a description of the strategy in quadrant 1 of the SWOT analysis, which means that the situation is very favorable in the problems that occur to make the strategy a solution to the problem by supporting an aggressive growth policy (Growth oriented strategy) in dealing with weaknesses and threats. The results of this study indicate that by collecting data on the entire stunting target every month as an indicator of surveillance readiness to cover 100% E-PPGBM data as evaluation material to obtain immediate treatment for each stunting case, implementing the Zero Growths Stunting Program by deploying State Civil Apparatus to play an active role in overseeing the surrounding environment that is at risk of stunting and is required to have stunted foster children, strictly enforcing the marriage dispensation application procedure and the existence of punishment for violations of the Marriage Law, implementing the Simultaneous Intervention Strategy to Accelerate the Reduction of Stunting in Jember Regency in 2024 which includes education for adolescents, the 1 family 1 fish pond program, building toilets, building uninhabitable houses, providing additional food, the one day one egg program, free health services and standardization of operational procedures for submitting marriage dispensations. And conduct education to conduct information technology selection to avoid free association and adultery, as well as providing higher education scholarships for underprivileged teenagers, as well as massive handling of underweight and wasting so that it does not become new stunting. So it will support aggressive growth policies in the strategies that have been designed. Researchers recommend assigning a letter of assignment to all surveillance in Jember Regency to ensure 100% stunting target data, assigning a letter of instruction to the family assistance team and state civil servants to carry out assistance to stunting targets and establishing an obligation for guardians to sign an integrity pact to prevent child marriage.